Case report: First report of Legionella pneumophila and Bordetella bronchiseptica coinfection in an immunocompromised patient - Marilena La Sorda; Ivana Palucci; Ivana Palucci; Daniele Natalini; Silvia Fillo; Francesco Giordani; Francesco Paglione; Francesco Paglione; Anella Monte; Florigio Lista; Fabiola Mancini; Antonietta Girolamo; et al. (Frontiers in Medicine, 2024)
Legionnaires' disease (LD) is a serious type of pneumonia, typically contracted by susceptible people through the inhalation of aerosols contaminated with Legionella pneumophila (Lp). In this report, the first case of coinfection with Lp–Bordetella bronchiseptica (Bb) is described. A possible source of the Lp infection may be the hotel in Paris (France) where the patient had stayed before developing the symptoms. The Bb infection may have been transmitted by the dog with which he had constant contact, although this has not been proven.